1971
DOI: 10.1126/science.172.3979.165
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Δ 8 - and Δ 9 -Tetrahydrocannabinol and Related Compounds in the Mouse

Abstract: The 11-hydroxy metabolites of Delta(8).- and Delta(9)-tetrahydrocannabinol are more active than the parent compounds when administered to mice by either the intravenous or intracerebral route. Both Delta(8)- and Delta(9)-tetrahydrocannabinol are rapidly and extensively metabolized by the liver and not by the brain. The hypothesis that the 11-hydroxy metabolites may be the active form of tetrahydrocannabinol is discussed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(40 citation statements)
references
References 12 publications
2
38
0
Order By: Relevance
“…Investigations in animals (12) Comparison of THC and its 11-OH Metabolite . 4 1 mal species this compound was shown to be pharmacologically active (13)(14)(15)(16)(17). Previous studies in man (2) have suggested that metabolites of A9-THC were actually responsible for the psychologic effects of Y9-THC and cannabis.…”
Section: Resultsmentioning
confidence: 99%
“…Investigations in animals (12) Comparison of THC and its 11-OH Metabolite . 4 1 mal species this compound was shown to be pharmacologically active (13)(14)(15)(16)(17). Previous studies in man (2) have suggested that metabolites of A9-THC were actually responsible for the psychologic effects of Y9-THC and cannabis.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, a major metabolite of A9-THC, 11-hydroxy-A9-THC, is thought to contribute significantly towards the pharmacological activity of its parent compound when the latter is administered to mice intravenously (Gill, Jones & Lawrence, 1973). However, when the parent compound is given intracerebrally or intraventricularly this is probably not so since conversion of A9-THC to its 11 -hydroxy metabolite in mouse brain is thought to be negligible (Christensen, Freudenthal, Gidley, Rosenfeld, Boegli, Testino, Brine, Pitt & Wall, 1971). …”
Section: Discussionmentioning
confidence: 99%
“…11-hydroxy-THC is rapidly formed by the action of hepatic microsomal oxidases, and plasma levels parallel the duration of observable drug action. 11-hydroxy-THC has been found to have psychotomimetic properties equal to THC (46)(47)(48). After smoking 1.75% and 3.55% THC cigarettes, this metabolite appears rapidly and peaks shortly after THC, approximately 15 min after the start of smoking (16).…”
Section: Metabolismmentioning
confidence: 99%